MURABAHAH LI AL-AMIR BI AL-SYIRA` AND ITS IMPLEMENTATION IN CONCEPT OF FINANCING AT SHARIA FINANCIAL INSTITUTIONS IN INDONESIA - Abdillah, Hary Hoiruman (Islamicate Institute, 2017)
In the classical Islamic jurisprudence, murabaha is one type of trading contract that is very simple, and the sale of murabahah is included in the type of sale and purchase of the equation because it requires the seller to be honest about the original price of the goods he is selling. In its current development, financing products at Sharia Financial Institutions in Indonesia are dominated by murabaha financing, this is because murabahah financing is considered safer and contains very little risk of loss. However, in practice murabahah financing at Sharia Financial Institutions is now experiencing innovation and modification compared with the basic concept that many contained in the literature of classical Jurisprudence, so that the term murabaha li al-aamir bi al-syira` which became the reference of contemporary murabaha financing. Although there are some differences but many contemporary scholars are allowing this contract, because in innovation and modification does not change the basic things. But not a few modification models that cause debate because it is done solely to meet the formal requirements of juridical for the consideration of the effectiveness and efficiency of banking administration. The following article will cover the various models and backgrounds and motives for shifting murabaha schemes in classical jurisprudence when practiced in sharia banking, in addition to explaining the use of murabahah schemes for various models of financing in sharia banking